Variation on morphology and spore characters of Dicranopteris and Sticherus (Gleicheniaceae) from Rokan Hulu District, Riau, Indonesia - Afni Atika Marpaung; Ratna Susandarini (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Marpaung AA, Susandarini R. 2021. Variation on morphology and spore characters of Dicranopteris and Sticherus (Gleicheniaceae) from Rokan Hulu District, Riau. Biodiversitas 22: 4475-4486. Dicranopteris and Sticherus are genera in the family Gleicheniaceae which have unique habits and distinctively specific growth with the presence of a bud on the forking branches. This study aims to reveal the species diversity of Gleicheniaceae members found in the forest area of Bukit Suligi Tandun, Rokan Hulu District, Riau and to document variations in their morphological characters and spores. Eleven collections were obtained from the exploration in the study area. The identification of plant specimens showed that these eleven taxa consisted of Dicranopteris curranii, Dicranopteris speciosa, seven varieties of Dicranopteris linearis, and two varieties of Sticherus truncatus. Seven varieties within D. linearis were D. linearis var. linearis, D. linearis var. alternans, D. linearis var. altissima, D. linearis var. demota, D. linearis var. inaequalis, D. linearis var. subspeciosa, and D. linearis var. tetraphylla. The only one species of Sticherus found was S. truncatus which consisted of two varieties, namely S. truncatus var. truncata and S. truncatus var. involuta. Morphological characters were observed from fertile specimens, while spore characters were observed from spore microscopic slides prepared using acetolysis method. There were 42 morphological characters and spores examined and used as the basis for determining the phenetic relationships using cluster analysis and principal component analysis. The results of cluster analysis showed the formation of two clusters that clearly separated the genus Sticherus from Dicranopteris. The three species of Dicranopteris were also clearly separated from each other in different sub-clusters. The result of principal component analysis indicated characters that contribute to the grouping of the eleven taxa and was able to explain the distinguishing characters in each group recognized from the cluster analysis. Overall, the results of this study contributed to documenting in detail the morphological variations in sporophyte and spore characters in eleven taxa of Dicranopetris and Sticherus, as well as proving the role of morphological and spore characters in the classification and defining phenetic relationships using numerical taxonomic approach.